Young children playing their way into intercultural understanding. (September 2019) - Acevedo, María V
Children's life experiences can position their exploration of global cultural communities within early childhood classrooms. Some early childhood educators, however, are concerned that many young children do not have direct experience of global cultures and thus believe that differences between cultural practices will be confusing to young children and global knowledge beyond their capacity. This study, conducted in a Reggio Emilia inspired preschool classroom in the Southwest United States, analysed young children's enquiries and intercultural understanding as they interacted and responded to an enquiry-based global curriculum. As a resource teacher conducting action research, I implemented the global curriculum and collected field notes, videos from children's play, artefacts that the children created as they engaged with the global curriculum and a teaching journal. I analysed the data, beginning with deductive categories from the professional literature, approaching intercultural understanding as knowledge, perspective and action. These broad categories were adapted and subcategories created to represent young children's intercultural understanding as evidenced through their play, enquiries and language. The findings of this study provide evidence to suggest that global exploration can enhance the lives of children when it: (1) builds on children's curiosity about the world and, through play, (2) highlights the development of knowledge, perspectives and action for a more just world.